From Collusion to Corruption: How Indonesian Law Fights Back in Procurement Conspiracy - Anggriawan, Rizaldy (Jurnal Penegakan Hukum dan Keadilan, 2025)
Government procurement of goods and services is one of the largest sectors in the state budgets, but it is vulnerable to corrupt practices. Based on data from Indonesia Corruption Watch (ICW), in 2017, there were 84 cases of corruption in the procurement of goods and services that caused state losses of IDR 1.02 trillion. This study aims to answer several main questions: what are the forms and indicators of collusion in government procurement of goods and services? How does the existing legal framework regulate and handle such collusive practices? Moreover, what legal sanctions are applied to perpetrators of violations? Using a normative method that examines related laws and regulations, this study uncovered that collusion in procurement occurs in three main forms: horizontal, vertical, and combined collusion. This study also reviews the role of the legal framework, including Law No. 5 of 1999 and Law No. 20 of 2001, which aims to create transparency and fair competition. The results of the study revealed that collusion in the procurement of goods and services violates the principles of fairness and transparency and suggests the need to strengthen regulations and supervision, including the active role of the Business Competition Supervisory Commission and the Corruption Eradication Commission. This synergy is expected to eradicate monopolistic practices and corruption while supporting clean and competitive governance.